-3(4b+1)=-63

Simple and best practice solution for -3(4b+1)=-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4b+1)=-63 equation:


Simplifying
-3(4b + 1) = -63

Reorder the terms:
-3(1 + 4b) = -63
(1 * -3 + 4b * -3) = -63
(-3 + -12b) = -63

Solving
-3 + -12b = -63

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -12b = -63 + 3

Combine like terms: -3 + 3 = 0
0 + -12b = -63 + 3
-12b = -63 + 3

Combine like terms: -63 + 3 = -60
-12b = -60

Divide each side by '-12'.
b = 5

Simplifying
b = 5

See similar equations:

| 12.00+-2.00x=10.00 | | 3p^2-5p-18=0 | | 35x^2=-x+6 | | 6v+11=3v+8 | | x+-29=1 | | 37-2(c+3)=4(c+5)+c | | 57*3=2x | | 18x+7(5x-9)+5(2x+7)+9=2x+5 | | -x-5=2x-5 | | 11+x=-19 | | 6(5p-2)=138 | | x+-44=-81 | | 98(-3)+98(3)=y | | -2w+8=-4w | | x+9x+4=0 | | 2+4lnx=12 | | 4x-2+5x+4=2x-3x+3-4 | | 5.2k=3.7+12.9 | | n+1=n | | -13+-5x=-43 | | -46+x=-72 | | 9x^2+22x-49-13x^2-8x+15= | | 12x+4=9+4x | | 9=2a+7 | | 6ln(7x)=13 | | -46+x=72 | | 2m^2-25m-90=0 | | p-4=-9+x | | 3(y+2)-2y=1 | | 3-x-x=-19 | | 42+x=65 | | 43=6x+1 |

Equations solver categories